Communicative language teaching clt activities for encouraging an improvement in the students oral expression from 1st course section A F at Eloy Alfaro high school academic year 2013 – 2014 - Plúas Saico, Andrea (2013)
Most Ecuadorian teachers are always looking for the best teaching methods, techniques, and strategies that can help students learn English as a foreign language. Communicative language teaching activities have been considered an essential tool for this study, because they set as a main goal, the use of the foreign language in different contexts, so students could effectively develop their abilities in the target language, focusing on the oral expression and communicative interaction. It is not only important to be aware of the grammatical rules, but students also need to face different language contexts, situations, and negotiate with meaningful codes at the moment of communicating……..